Walgreens Boots Alliance, Inc. : retail trade in unregulated dietary supplements - Ludwig, Carson, (SAGE Business Cases., 2019)
Dietary supplements are a billion dollar unregulated industry. Walgreens Boots Alliance earns millions in revenue each year in its retail pharmacies from the sale of such supplements. Consumers who take dietary supplements often do so with the intention of protecting and improving their health. Most consider these products to be safe and free of side effects. Dietary supplements, however, can have adverse or toxic effects due to the lack of regulation surrounding ingredient labeling, level of contaminants, and consistency of ingredients across products. What obligations does Walgreens have to supervise or reveal any of this to its trusting customers?